Complete genome sequence of Tunisvirus, a new member of the proposed family Marseilleviridae - Sarah Aherfi; Mondher Boughalmi; Isabelle Pagnier; Ghislain Fournous; Bernard La Scola; Didier Raoult; Philippe Colson (Archives of Virology, 2014)

Complete genome sequence of Courdo11 virus, a member of the family Mimiviridae - Niyaz Yoosuf; Isabelle Pagnier; Ghislain Fournous; Catherine Robert; Bernard La Scola; Didier Raoult; Philippe Colson (Virus Genes, 2014)

Complete genome sequence of Cannes 8 virus, a new member of the proposed family “Marseilleviridae” - Sarah Aherfi; Isabelle Pagnier; Ghislain Fournous; Didier Raoult; Bernard La Scola; Philippe Colson (Virus Genes, 2013)

Local adaptation of sex induction in a facultative sexual crustacean: insights from QTL mapping and natural populations of D aphnia magna - Anne C. Roulin; Jarkko Routtu; Matthew D. Hall; Tim Janicke; Isabelle Colson; Christoph R. Haag; Dieter Ebert (Molecular Ecology, 2013)
Dormancy is a common adaptation in invertebrates to survive harsh conditions. Triggered by environmental cues, populations produce resting eggs that allow them to survive temporally unsuitable conditions. D aphnia magna is a crustacean that reproduces by cyclical parthenogenesis, alternating between the production of asexual offspring and the sexual reproduction of diapausing eggs (ephippia). Prior to ephippia production, males (necessary to ensure ephippia fertilization) are produced parthenogenetically. Both the production of ephippia and the parthenogenetic production of males are induced by environmental factors. Here, we test the hypothesis that the induction of D . magna resting egg production shows a signature of local adaptation. We postulated that D aphni a from permanent ponds would produce fewer ephippia and males than D aphnia from intermittent ponds and that the frequency and season of habitat deterioration would correlate with the timing and amount of male and ephippia production. To test this, we quantified the production of males and ephippia in clonal D . magna populations in several different controlled environments. We found that the production of both ephippia and males varies strongly among populations in a way that suggests local adaptation. By performing quantitative trait locus mapping with parent clones from contrasting pond environments, we identified nonoverlapping genomic regions associated with male and ephippia production. As the traits are influenced by two different genomic regions, and both are necessary for successful resting egg production, we suggest that the genes for their induction co‐evolve.

High‐throughput isolation of giant viruses of the M imiviridae and M arseilleviridae families in the T unisian environment - Mondher Boughalmi; Hanene Saadi; Isabelle Pagnier; Philippe Colson; Ghislain Fournous; Didier Raoult; Bernard La Scola (Environmental Microbiology, 2013)
Summary Giant viruses of the M egavirales order have been recently isolated from aquatic environments and have long been neglected because they are removed from samples during viral purification for viral metagenomic studies. Due to bacterial overgrowth and susceptibility to high concentrations of antibiotics, isolation by amoeba co‐culture has a low efficiency and is highly time‐consuming. Thus, few environments have been exhaustively investigated to date, although the ubiquitous distribution of the A canthamoeba sp. suggests that these viruses could also be ubiquitous. In this work, we have implemented a high‐throughput method to detect amoebae lysis on agar plates that allows the testing of hundreds of samples in a few days. Using this procedure, a total of 11 new M arseilleviridae strains and four new M imiviridae strains, including a virus infected with a virophage, were isolated from 1000 environmental samples from T unisia. Of these, four corresponded to new genotypic variants. These isolates are the first A frican environmental isolates identified from these two families, and several samples were obtained from a hypersaline aquatic environment. These results demonstrate that this technique can be used for the evaluation and characterization of large collections of giant viruses to provide insight into understanding their ecology.

“Marseilleviridae”, a new family of giant viruses infecting amoebae - Philippe Colson; Isabelle Pagnier; Niyaz Yoosuf; Ghislain Fournous; Bernard La Scola; Didier Raoult (Archives of Virology, 2013)

The evolutionary mechanism maintaining shell shape and molecular differentiation between two ecotypes of the dogwhelk Nucella lapillus - Jorge Guerra-Varela; Isabelle Colson; Thierry Backeljau; K. Breugelmans; Roger N. Hughes; Emilio Rolán-Alvarez (Evolutionary Ecology, 2009)

Drosophila simulans' response to laboratory selection for tolerance to a toxic food source used by its sister species D. sechellia - Isabelle Colson (Evolutionary Ecology, 2004)